Population Densities Of Agile Gibbon (Hylobates Agilis) And Their Relationship With Habitat Characteristics And History Of Disturbance In The Ulu Muda Forest Reserve, Malaysia - Pang, Yi Heng (2022)
The population of small ape species in Peninsular Malaysia has not been studied since the early 1980s, while many of their habitats are increasingly being converted for other land use types. This study aims to estimate the total number of agile gibbons (Hylobates agilis) groups in areas below 450 m above sea level within Ulu Muda Forest Reserve (UMFR), Kedah. The group densities in different parts of UMFR with different degrees of disturbance were compared. Bioacoustic surveys were conducted in nine study sites to estimate group density, while vegetation “speed plots” and satellite imagery were used to qualify habitat characteristics. The group density in UMFR ranged from 3.89 to 4.17 groups per km2 (95% C.I.), and did not show any significant difference among forest types (p = 0.27). The best ecological predictors for group density were “canopy cover” and “proportion of area deforested”.